2019
DOI: 10.1017/jfm.2019.205
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds-averaged Navier–Stokes equations with explicit data-driven Reynolds stress closure can be ill-conditioned

Abstract: Reynolds-averaged Navier-Stokes (RANS) simulations with turbulence closure models continue to play important roles in industrial flow simulations. However, the commonly used linear eddy viscosity models are intrinsically unable to handle flows with nonequilibrium turbulence (e.g., flows with massive separation). Reynolds stress models, on the other hand, are plagued by their lack of robustness. Recent studies in plane channel flows found that even substituting Reynolds stresses with errors below 0.5% from dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(90 citation statements)
references
References 40 publications
2
88
0
Order By: Relevance
“…Nevertheless, a unique challenge for directly correcting or predicting the Reynolds stress tensors with data-driven models is the possible ill-conditioning of the RANS equations. For example, small errors in the machine-learning-predicted Reynolds stresses can lead to large errors in the propagated velocities [146]. In order to overcome this difficulty, Wu et al [123] proposed learning the linear and nonlinear parts of the Reynolds stress separately, with the linear part treated implicitly to improve model conditioning.…”
Section: Quantifying and Reducing Reynolds Stress Uncertainties With mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a unique challenge for directly correcting or predicting the Reynolds stress tensors with data-driven models is the possible ill-conditioning of the RANS equations. For example, small errors in the machine-learning-predicted Reynolds stresses can lead to large errors in the propagated velocities [146]. In order to overcome this difficulty, Wu et al [123] proposed learning the linear and nonlinear parts of the Reynolds stress separately, with the linear part treated implicitly to improve model conditioning.…”
Section: Quantifying and Reducing Reynolds Stress Uncertainties With mentioning
confidence: 99%
“…On the other hand, Wang et al [186] performed the same propagation for fully developed turbulent flows in square ducts at various Reynolds numbers and found that the propagated velocities agree with DNS data satisfactorily. Such apparently conflicting findings were explained by different model conditioning in various flows, i.e., different sensitivity levels of the mean velocities to Reynolds stresses [146].…”
Section: Appendix a Algorithms In Uncertainty Quantificationmentioning
confidence: 99%
“…Such an approach does not constrain our work to model-specific assumptions. We note that explicit R-S approaches can potentially result in significant prediction error of fluid quantities when the Reynolds number approaches 5000 and above [26,27]. Additionally, small errors in the predicted R-S field in an explicit representation can be amplified leading to instabilities.…”
Section: Invariant Neural Networkmentioning
confidence: 93%
“…9-10. As the R-S is increased, minor deviations in the anisotropic term are amplified resulting in potentially starkly different flow predictions [27]. SDD-RANS accurately captures these phenemona.…”
Section: Backwards Stepmentioning
confidence: 99%
See 1 more Smart Citation